Phosphorothioate DNA Mediated Sequence-Insensitive Etching and Ripening of Silver Nanoparticles - Hu, Shengqiang; Huang, Po-Jung Jimmy; Wang, Jianxiu; Liu, Juewen (Frontiers in Chemistry, 2019)
While various DNA-functionalized nanomaterials and biosensors have been reported, most of them ignored the influence of DNA on the stability of nanoparticles. We recently noticed that cytosine and guanine rich DNA oligonucleotides can etch silver nanoparticles (AgNPs). In this work, we communicated that phosphorothioate (PS) modified DNA (PS-DNA) could etch AgNPs quite independent of DNA sequence, suggesting that the thio modifications were playing the major role of etching. Compared to the normal DNA (e.g. poly-C DNA), the required concentration decreased sharply and the reaction rate increased. Furthermore, the etching occurred regardless of pH, which was also different from the unmodified DNA. The PS-DNA mediated etching also could be well controlled by varying DNA length and conformation, and the number and location of PS modifications. With higher ability to etch, we observed etching-ripening-further etching. The ability to etching was inhibited by forming duplex DNA and thus etching can be used to measure the concentration of complementary DNA.